The relationship of cannabis decriminalization in Colorado and cannabis use in individuals with alcohol use disorders - Jeremy T. Hua; Majid Afshar; Brendan J. Clark; Elizabeth J. Kovacs; Ellen L. Burnham (BMC, 2020)
Abstract Objective Over the past decade, cannabis use has become increasingly popular in states that include Colorado. During this time, alcohol use disorders (AUDs) and alcohol-related medical conditions have also been consistently recognized as public health problems with increasing prevalence in the state. Despite the widespread use of cannabis in Colorado, the epidemiology of cannabis use among those with AUDs has been poorly described. Therefore, we sought to examine cannabis use among individuals with likely AUDs and individuals with low-risk alcohol use during a time of major Colorado legislative changes before and after legalization of recreational cannabis in 2012. Methods This study was a secondary data analysis conducted with information from 303 participants (80% male) in the Denver, CO metropolitan enrolled between August 2007 and April 2016 for studies related to alcohol and lung health. Of these participants, 188 (62%) were completing inpatient alcohol detoxification with likely AUDs. All participants completed the Alcohol Use Disorder Identification Test (AUDIT) to establish their likelihood of an AUD, and all had information on current cannabis use assessed by questionnaire and urine toxicology testing. Results Individuals with likely AUDs more commonly used cannabis compared to control participants (42% vs 27%, p = 0.007). In multiple logistic regression analyses, participant type (likely AUD versus control), tobacco smoking, and age were significantly associated with cannabis smoking; however, the year of participant enrollment was not. Adjusted odds for cannabis use among participants with likely AUDs were 2.97 (1.51-5.82), p = 0.002, while odds for cannabis use among tobacco smokers were 3.67 (1.94-6.93), p < 0.0001. Among control participants, tobacco smoking increased odds of cannabis use seven-fold. Conclusions Our findings highlight the exceptionally high odds of cannabis use among individuals with likely AUDs undergoing alcohol detoxification at a Colorado treatment facility before and after legalization of recreational cannabis. Targeted investigations into the medical and psychiatric consequences of combined alcohol and cannabis use are urgently needed to define its health impact in these vulnerable individuals.